Integration of the Bride and the Courts: Is Integration as Living Customary Law Requirement Still Required? - Bakker, Pieter (Potchefstroom Electronic Law Journal, 2022)
After 15 November 2000, a customary marriage must satisfy the provisions of section 3(1) of the Recognition of Customary Marriages Act 120 of 1998. Section 3(1)(b) incorporates the living customary law requirements into the Act. The publication explores whether handing over of the bride to the bridegroom’s family is still required, based on two recent judgements from the South African Supreme Court of Appeal in two judgements: Mbungela v Mkabi 2019 ZASCA 134 and Tsambo v Sengadi In re: Tsambo 2020 ZASCA 46. The author argues that a clear distinction must be made between rituals and requirements when determining whether a customary marriage is valid under the living customary law. The author argues that Mbungela v Makabi is wrong in law and therefore not authority that "handing over in the wide sense" (or integration) is not required for the conclusion of a valid customary marriage. Tsambo v Sengadi In re: Tsambo is correct. Concluding that although the rituals of handing over (handing over in the narrow sense) can be amended, abbreviated, or waived the parties still have to comply with integration of the bride into the bridegroom’s family for a valid customary marriage to take place. The author supports the revival of the presumption of a valid customary marriage if the couple cohabited after the lobolo negotiations are completed and the woman’s family has not objected.